2016
DOI: 10.3983/twc.2016.0669
|View full text |Cite
|
Sign up to set email alerts
|

Swan Queen, shipping, and boundary regulation in fandom

Abstract: There are a number of fan activities and practices that are subject to regulation. The mechanisms of regulation in shipping, however, are not always clear. Shipping, the fan activity of romantically pairing two fictional characters, has become a popular and contentious facet of fan interaction. The case that will be examined in this article is that of the Swan Queen ship, which pairs two female characters from Once Upon a Time (2011–). The lengths that fans have gone to support and promote this ship led to rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Beyond the formation of parasocial relationships and personally identifying with fictional characters, readers of popular fiction may emotionally invest in stories in a variety of ways, including becoming highly invested in fictional relationships (e.g., Gonzalez, 2016) or wishing to visit or know more about a given fictional world (e.g., Mittell, 2009, 2013). Regardless of the exact way in which a reader emotionally invests in a fictional story, it seems likely that any enduring emotional connection to a work of fiction may increase a given reader's motivation to imaginatively engage with the narrative.…”
Section: Fiction and Social Cognitionmentioning
confidence: 99%
“…Beyond the formation of parasocial relationships and personally identifying with fictional characters, readers of popular fiction may emotionally invest in stories in a variety of ways, including becoming highly invested in fictional relationships (e.g., Gonzalez, 2016) or wishing to visit or know more about a given fictional world (e.g., Mittell, 2009, 2013). Regardless of the exact way in which a reader emotionally invests in a fictional story, it seems likely that any enduring emotional connection to a work of fiction may increase a given reader's motivation to imaginatively engage with the narrative.…”
Section: Fiction and Social Cognitionmentioning
confidence: 99%
“…More recent studies observe that this is not always the case. These studies find that discrimination and marginalization are common in fan communities and these conflicts often lead to the fragmenting of fandoms into smaller communities with niche interests (Boethe 2014; Gonzalez 2016).…”
Section: Case Overviewmentioning
confidence: 99%
“…Kristina Busse (2013) contends that both gender and sexuality are policed in fandom, with feminized practices considered inappropriate and women’s sexual desire marginalized by contemporary moves toward mainstreaming fans as ideal consumers. More intensively, Julie Levin Russo (2017, 160) is critical of the ways fan studies “positions not necessarily queer-identified women writing about not necessarily queer-identified men as more queer than people who are queer.” Indeed, Victoria Gonzalez (2016, 1.1) contests the baseline idea of fandom as sexually progressive, pointing out that “within fandom communities not all ships or shippers are created equal and some are in fact deemed more rabid than others”—and these ships tend to be the queer ones.…”
Section: Fandom Is (Sometimes) Uglymentioning
confidence: 99%
“… 2. There is, however, a growing body of research on antagonism (Johnson 2007) and inequality (Busse 2013; Gonzalez 2016; Pande 2016; Stanfill 2018) in fandom. …”
mentioning
confidence: 99%